Implementing Home Health Monitoring for Chronic Disease Management in British Columbia - Winnie Ma (McMaster University Library Press, 2022)
Home health monitoring (HHM) enables health care providers to monitor a patient's health status remotely using digital technology. In 2013, the government of British Columbia (BC) partnered with a telecommunications provider and invested $52M in HHM programs for patients with complex care needs. Telehealth has evolved over the past two decades to improve access and delivery of care, with HHM emerging as a strategy for proactive chronic disease management. The goals of the provincial HHM initiative are to reduce acute care utilization, reduce health system costs and improve patient self-management of chronic conditions. Following a series of successful pilot projects, funding for expanded HHM initiatives was made available through a provincial Strategic Investment Fund and continued support from Canada Health Infoway. Evaluations of several HHM programs demonstrated high levels of patient satisfaction, reduced emergency department visits, health system cost savings, and improved patient self-care and quality of life. Optimizing referral rates and expanding HHM programs to include a wider range of chronic conditions are opportunities for future growth, with sustainability dependent on securing long-term funding sources.